Inner bars also buckle. The MUSE TIMER view of the double-barred galaxy NGC 1291. (18th October 2018) - Méndez-Abreu, J; de Lorenzo-Cáceres, A; Gadotti, D A; Fragkoudi, F; van de Ven, G; Falcón-Barroso, J; Leaman, R; Pérez, I; Querejeta, M; Sánchez-Blazquez, P; Seidel, M
Abstract: Double bars are thought to be important features for secular evolution in the central regions of galaxies. However, observational evidence about their origin and evolution is still scarce. We report on the discovery of the first Box/Peanut (B/P) structure in an inner bar detected in the face-on galaxy NGC 1291. We use the integral field data obtained from the MUSE spectrograph within the TIMER project. The B/P structure is detected as bi-symmetric minima of the h 4 moment of the line-of-sight velocity distribution along the major axis of the inner bar, as expected from numerical simulations. Our observations demonstrate that inner bars can follow a similar evolutionary path as outer bars, undergoing buckling instabilities. They also suggest that inner bars are long-lived structures, thus imposing tight constraints to their possible formation mechanisms.